The Role of Temporary Marriage in the Formation of a ‘Modern’ Islamic Sexual and Relational Ethics for Halal Dating among Young Pious Muslim Men - Lechkar, Iman (Religion & gender, 2022)
This article explores the role of temporary marriage in the formation of a ‘modern’ Islamic sexual and relational ethics for ‘halal’ (religiously permissible) dating. Based on ethnographic research on the Shiitization (at-tashayyu’) of Moroccan Belgian Sunni Muslims, this article argues that temporary marriage is endorsed by young pious Muslim men who want to date in a religiously observant way. This article illustrates how temporary marriage figures as a site for private relationships and a framework for a modern sexual and relational ethics that permits halal dating for young Muslims. The call of young pious Muslim men to a general Muslim endorsement of temporary marriage brings together both their secular and religious sensibilities whilst simultaneously endeavoring to undo the Sunni-Shia divide in terms of sexual and relational ethics. By drawing on Joan W. Scott’s notion of ‘sexularism’, this article not only deflates the sharp opposition between Islam and secularity, but also provides analytical strategies that disentangle commonplace tropes surrounding Islam and the (sexual) oppression of women.